1981
DOI: 10.1295/polymj.13.493
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Ferroelectric Polarization Switching in Poly(vinylidene fluoride)

Abstract: Ferroelectric polarization switching experiments were carried out on Form I crystal of poly(vinylidene fluoride) over a temperature range from-76°C to 125oC and at applied electric fields E up to 200 MV m-1. At 25°C, notable polarization switching currents which decayed within a few ms were observed at MVm-1 These currents became more intensive with increasing applied electric field. The maximum switching current density ]max and the maximum switching time rmax could be expressed approximately by ]max (Am-2)=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The influence of the state of the disordered phase on the switching parameters has also been studied by Matsushige et al, 55 who derived switching characteristics from the time variation of the transpolarisation current at the same field strength (200 MV m 71 ). Three temperature regions of variation of t s characterised by different activation energies of the switching process can be distinguished.…”
Section: Characteristic Features Of the Polarisation Switching Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the state of the disordered phase on the switching parameters has also been studied by Matsushige et al, 55 who derived switching characteristics from the time variation of the transpolarisation current at the same field strength (200 MV m 71 ). Three temperature regions of variation of t s characterised by different activation energies of the switching process can be distinguished.…”
Section: Characteristic Features Of the Polarisation Switching Processesmentioning
confidence: 99%
“…The time t (like the normal relaxation time) decreases as the temperature increases, which can also affect the temperature dependence of the switching time t s . 55 The above mechanism for the generation and development of domains in the switching processes does not take into account the effect of the space charge formed by both the inherent charge carriers and those injected from the electrodes during poling. However, experimental results imply that this effect cannot be neglected.…”
Section: Characteristic Features Of the Polarisation Switching Processesmentioning
confidence: 99%
“…Using our compressibility data, Matsushige et a/. 4 showed that the pressure dependence of the polarization switching time can be well explained by the pressure dependence of the free volume in the amorphous part, and suggested that the polarization reversal mechanism is closely related to molecular motions in the amorphous part rather than in the crystalline part. Thus, the polarization reversal begins pref-erentially at the boundary between the crystalline and amorphous parts and/or at the defects in the sample.…”
Section: Compressibilitymentioning
confidence: 70%
“…obtain a basic understanding of this mechanism. 4 For this purpose, changes in the free volume of the crystalline and amorphous parts with pressure are the most important quantities that had to be evaluated. Furthermore, according to the composite model theory, 5 P-V-Tequations of state for the two parts and the pressure dependence of their dielectric properties should be closely related to piezoelectric and pyroelectric properties under high pressure.…”
Section: Procedures Of Analysismentioning
confidence: 99%
See 1 more Smart Citation